Peningkatan pembelajaran keterampilan berbicara melalui media gambar seri di kelas I - Zarlianti Zarlianti (JPGI (Jurnal Penelitian Guru Indonesia), 2019)
The goal is that students are brave, accustomed to being able to speak in all functions according to proper pronunciation and intonation Data collection is carried out by tests, observations or observation sheets and other supporting instruments of research. This study uses a qualitative approach with a type of classroom action research. The research subjects were first grade students of SDN. 08 Painan District IV Jurai. Based on the results of the study, the serial image media can improve students' speaking skills with three-stage learning activities, namely: (1) initial activities, (2) core activities, and (3) final activities. The result of the first cycle of research based on the implementation of the lesson plan is 76.8% and the recapitulation of student learning assessment is 74%. The results of the second cycle research based on the implementation of lesson plans were 83.9% and the recapitulation of the assessment process and student learning outcomes was 83%. From the results of observations and recapitulation of values obtained by students, it appears that students are active in the learning process.